2016
DOI: 10.1161/circep.115.003337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Complete Versus Incomplete Circumferential Lines Around the Pulmonary Veins During Catheter Ablation of Paroxysmal Atrial Fibrillation

Abstract: Background— Ablation of atrial fibrillation (AF) is an established treatment option for symptomatic patients. It is not known whether complete pulmonary vein isolation (PVI) is superior to incomplete PVI with regard to the patients’ clinical outcome. Methods and Results— Patients with drug-refractory, symptomatic paroxysmal AF were randomly assigned to either incomplete (group A) or complete PVI (group B). In group A, a persistent gap was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 231 publications
(165 citation statements)
references
References 36 publications
5
157
0
3
Order By: Relevance
“…The difference between the surgical and the radiofrequency current ablation approach is that surgical PVI is permanent, whereas radiofrequency current-induced PVI at the index procedure is associated with a high likelihood of reconduction from the PVs to the LA through gaps in the circumferential ablation lines. 19 In this study, conduction gaps were found in 80% of patients undergoing repeat ablation, indicating that the development of conduction gaps along the ablation lines is the dominant mechanism of AF recurrence after radiofrequency current-induced PVI in both ablation strategies. Therefore, the demonstration of a potential longterm benefit of additional substrate modification at the time of PVI is prevented by the high reconduction rate through gaps in the PVI lines.…”
Section: The Substrate-modification Strategy Failed To Reduce Arrhythmentioning
confidence: 57%
“…The difference between the surgical and the radiofrequency current ablation approach is that surgical PVI is permanent, whereas radiofrequency current-induced PVI at the index procedure is associated with a high likelihood of reconduction from the PVs to the LA through gaps in the circumferential ablation lines. 19 In this study, conduction gaps were found in 80% of patients undergoing repeat ablation, indicating that the development of conduction gaps along the ablation lines is the dominant mechanism of AF recurrence after radiofrequency current-induced PVI in both ablation strategies. Therefore, the demonstration of a potential longterm benefit of additional substrate modification at the time of PVI is prevented by the high reconduction rate through gaps in the PVI lines.…”
Section: The Substrate-modification Strategy Failed To Reduce Arrhythmentioning
confidence: 57%
“…When interpreting results from studies evaluating novel ablation strategies, it seems important to recognise a major limitation of current catheter ablation interventions: Even when the PVI is performed in selected, highly experienced centres with a clear aim to achieve complete isolation, this is only achieved in a minority of patients. 72 Hence, better technology is needed to achieve transmural lesions. This has implications not only for the evaluation of linear lesions but also for other ablation concepts.…”
Section: Targets For Catheter Ablation Beyond Pulmonary Vein Isolationmentioning
confidence: 99%
“…8,9 A recent study proved the superiority of complete PVI over incomplete PVI with respect to AF recurrence. 10 Methods to detect incomplete reversible lesions in clinical practice remain to be fully clarified. The presence of dormant conduction in response to adenosine or ATP that hyperpolarizes atrial cell membranes and triggers transient conduction, might indicate incomplete cell injury.…”
Section: Importance Of Durable Lesion Formationmentioning
confidence: 99%